(untitled) (Advancements in Homeopathic Research, 2025)
This article offers an overview of the background and current landscape of standardization in the field of Homoeopathy. It highlights the roles of regulatory authorities and examines the initiatives undertaken by the Bureau of Indian Standards. Additionally, the article discusses the recently published Indian Standards related to Homoeopathy, emphasizing their significance and impact. The implications of these standards for stakeholders are explored, along with a perspective on future developments in this area.